Calculating mean length of utterance for eastern Canadian Inuktitut. Issue 4 (October 2015) - Allen, Shanley E. M.; Dench, Catherine
Although virtually all Inuit children in eastern Arctic Canada learn Inuktitut as their native language, there is a critical lack of tools to assess their level of language ability. This article investigates how mean length of utterance (MLU), a widely-used assessment measure in English and other languages, can be best applied in Inuktitut. The authors seek a measure that is suitable for the structural characteristics of Inuktitut as well as the practical realities of language assessment in the Inuit context. They compare five measures of mean length of utterance/word as well as five measures of longest utterance/word using three sets of data: spontaneous speech from eight children aged 1;8–3;6, frog story narratives from 12 older children and 6 adults, and spontaneous speech from one 5-year-old with specific language impairment and an age-matched peer. The authors conclude that mean length of word in syllables is the measure that provides the best balance of reliably assessing language level while also suiting Inuktitut structure and being relatively easy to calculate.